<htm>Bembicine wasps (Crabronidae, Bembicinae) of Marambaia Island (Mangaratiba, RJ, Brazil): preliminary inventory of species and bionomic notes</htm> - Guimarães, Ronald Rodrigues; Buys, Sandor Christiano; Vivallo, Felipe; Guimarães Junior, Ronald Rodrigues; Rodrigues, Harlan Ronald Storti; Guimarães, Roney Rodrigues; Seppa, Gilberto dos Santos; Carvalho, Raimundo Wildon de (Acta Biológica Paranaense, 2014)
<htm>Bembicine wasps (Crabronidae, Bembicinae) of Marambaia Island (Mangaratiba, RJ, Brazil): preliminary inventory of species and bionomic notes</htm>